Thematic Maps of the Impact of Urbanization and Socioeconomic Factors on the Distribution of the Incidence of Cutaneous Leishmaniasis Cases in Sefrou Province, Central North of Morocco (2007–2011) - Fatima Zahra Talbi; Nordine Nouayti; Hajar El Omari; Mohamed Najy; Khadija Lahouiti; Mouhcine Fadil; Hassan Ech-Chafay; Mohamed Lachhab; Abdellatif Janati Idrissi; Abdelhakim El Ouali Lalami (Interdisciplinary Perspectives on Infectious Diseases)
Background. Leishmaniases are vector-borne diseases with health risks. They cause a big health problem. These parasitic diseases are transmitted by the parasite of the genus Leishmania through sandflies. Objective. The aim of this work is to study the distribution of the incidence of cutaneous leishmaniasis (CL) cases and the impact of urbanization and socioeconomic factors and their effects as leishmaniasis risk factors. Methods. We conducted a retrospective study of CL cases collected at the level of Sefrou Province during the period from 2007 to 2011. The data was collected from registers of the Medical Delegation of Sefrou Province. The socioeconomic data, namely, the poverty rate, the popular density, and the type of environment (urban/rural) of Sefrou Province, were obtained from the High Commission for Planning. Statistical analysis was performed by SPSS software (version 20). The data were registered in a Microsoft Excel 2010 file. Statistical analysis was based on one-way analysis of variance (ANOVA), and then a correlation study was carried out (Pearson correlation). The results were considered significant when p was less than 0.05. The database was analyzed by QGIS 2.18, which is open source software. Results. A total of 349 cases of CL were collected at Sefrou Province from 2007 to 2011. A percentage of 49% of the cases come from urban areas, while 51% of the cases come from rural areas. In the statistical analysis, the division of the incidence of CL cases was found to be significantly associated only with urbanization. For the other factors, the number of people or the poverty rate is not taken into account in the incidence dynamics. Conclusion. This study may be useful for the implementation of future adequate measures and controls. Getting rid of leishmaniasis requires a comprehensive approach by acting on the sources of contamination through good continuous surveillance, appropriate management, effective vector control, and awareness-raising strategies.